Percutaneous closure of a paravalvular leak from a prosthetic mitral valve dehiscence in a young high-risk patient: case report. Issue 7 (16th June 2022) - Ozden, Ozge; Kemal, Hatice; Bingöl, Gülsüm; Göktekin, Ömer
Abstract: Background: Paravalvular leak (PVL) is a common, serious complication related with prosthetic valve replacement. Although surgical closure reoperation is the choice of treatment, percutaneous device closure is a good alternative with good results in patients with very high surgical risk. Case summary: In this case report, we present the percutaneous closure of PVL of mitral valve replacement (MVR), in a patient with cardiogenic shock who failed conservative medical treatment and was deemed inoperable due to recurrent operations. Successful closure of the PVL with the use of the four consecutive PVL closure devices was performed under general anaesthesia with guidance of 2D and 3D transoesophageal echocardiography. The procedure was performed with no complications and the patient has remained asymptomatic after 10 months following the PVL closure procedure with marked improvement in her NYHA class and echocardiographic values. Discussion: Percutaneous PVL closure is a very challenging and high clinical skills requiring procedure, but has a good success and low complication rate in high-risk patients. It is not a standard procedure and the type and size of device should be tailored for each patient with a good 2D and 3D echocardiographic guidance.